Temperature-controlled propagation of spikes in neuronal networks. (November 2022) - Yao, Chenggui; Yao, Yuangen; Qian, Yu; Xu, Xufan
Abstract: Temperature plays a vital role in the functioning of biological organisms and there often exists an optimal temperature for their best performance. In this work, we investigate the role of temperature on spike propagation in scale-free and small-world neuronal networks, where a single neuron is chosen randomly for receiving a stimulus current. Upon exploiting the dominant phase-advanced driving (DPAD) method, the complex neuronal network is seen as a regular feed-forward multilayer neuronal network. The propagation route is then clearly identified, and many traveling-like waves are formed along the propagation route. Interestingly, we find that temperature not only controls the shortest path of propagation but also regulates the response time of a single neuron. The propagation speed is also maximized for an optimal choice of temperature at which the spike rapidly propagates through the entire neuronal network. Our findings extend the current understanding of the neuronal networks functioning and provide new insights into the existence of an optimal temperature as seen in our experiments on several living biological systems. Highlights: Applying the dominant phase-advanced driving method, the complex neuronal network can be organized as a feed-forward network. Many traveling-like waves are formed along the propagation route in the complex network. Temperature can not only optimize the shortest path of propagation, but also regulate the response time of a single neuron. The velocity of spiking propagation is maximized for an optimal choice of the temperature.